Brown tumor of the jaw after pregnancy and lactation in a MEN1 patient. (16th November 2016) - Casteràs, Anna; Darder, Lídia; Zafon, Carles; Hueto, Juan Antonio; Alberola, Margarita; Caubet, Enric; Mesa, Jordi
Summary: Skeletal manifestations of primary hyperparathyroidism (pHPT) include brown tumors (BT), which are osteoclastic focal lesions often localized in the jaws. Brown tumors are a rare manifestation of pHTP in Europe and USA; however, they are frequent in developing countries, probably related to vitamin D deficiency and longer duration and severity of disease. In the majority of cases, the removal of the parathyroid adenoma is enough for the bone to remineralize, but other cases require surgery. Hyperparathyroidism in MEN1 develops early, and is multiglandular and the timing of surgery remains questionable. To our knowledge, there are no reports of BT in MEN 1 patients. We present a 29-year-old woman with MEN 1 who developed a brown tumor of the jaw 24 months after getting pregnant, while breastfeeding. Serum corrected calcium remained under 2.7 during gestation, and at that point reached a maximum of 2.82 mmol/L. Concomitant PTH was 196 pg/mL, vitamin D 13.7 ng/mL and alkaline phosphatase 150 IU/L. Bone mineral density showed osteopenia on spine and femoral neck (both T -scores = −1.6). Total parathyroidectomy was performed within two weeks, with a failed glandular graft autotransplantation, leading to permanent hypoparathyroidism. Two months after removal of parathyroid glands, the jaw tumor did not shrink; thus, finally it was successfully excised. We hypothesize that higher vitamin D and mineral requirements during maternity may have triggered an accelerated bone resorption followed by appearance of the jaw BT. We suggest to treat pHPT before planning a pregnancy in MEN1 women or otherwise supplement with vitamin D, although this approach may precipitate severe hypercalcemia. Learning points: Brown tumors of the jaw can develop in MEN 1 patients with primary hyperparathyroidism at a young age (less than 30 years). Pregnancy and lactation might trigger brown tumors by increasing mineral and vitamin D requirements. Early parathyroidectomy is advisable in MEN 1 patients with primary hyperparathyroidism, at least before planning a pregnancy. Standard bone mineral density does not correlate with the risk of appearance of a brown tumor. Removal of parathyroid glands does not always lead to the shrinkage of the brown tumor, and surgical excision may be necessary.